2011
DOI: 10.1152/ajpregu.00045.2011
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic potential of hydrogen sulfide: separating hype from hope

Abstract: Hydrogen sulfide (H2S) has become the hot new signaling molecule that seemingly affects all organ systems and biological processes in which it has been investigated. It has also been shown to have both proinflammatory and anti-inflammatory actions and proapoptotic and anti-apoptotic effects and has even been reported to induce a hypometabolic state (suspended animation) in a few vertebrates. The exuberance over potential clinical applications of natural and synthetic H2S-“donating” compounds is understandable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
155
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(162 citation statements)
references
References 204 publications
(174 reference statements)
3
155
0
4
Order By: Relevance
“…Recent studies have shown that exogenous hydrogen sulfide (H 2 S) initiates pharmacophysiological responses in most, if not all, organ systems (Li et al, 2011;Olson, 2011). These studies have been instrumental in the hypothesis that hydrogen sulfide is a biologically relevant signaling molecule thereby joining nitric oxide (NO) and carbon monoxide (CO) as 'gasotransmitters' (Wang, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that exogenous hydrogen sulfide (H 2 S) initiates pharmacophysiological responses in most, if not all, organ systems (Li et al, 2011;Olson, 2011). These studies have been instrumental in the hypothesis that hydrogen sulfide is a biologically relevant signaling molecule thereby joining nitric oxide (NO) and carbon monoxide (CO) as 'gasotransmitters' (Wang, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen sulfide has been proposed as a gaseous signaling molecule along with nitric oxide and carbon monoxide (1). A number of studies suggested therapeutic potential of H 2 S-donating compounds and H 2 S gas itself for a number of animal models of human disease including ischemic brain injury (2,3).…”
Section: Physiological Levels Of H 2 S Exert Neuroprotective Effectsmentioning
confidence: 99%
“…Gaseous H 2 S, however, may be difficult to be used clinically because of its characteristic odor and toxicity at high concentrations (1,4). Na 2 S and sodium hydrosulfide (NaHS) have been used as H 2 S donor compounds in the majority of experimental studies (2,3).…”
Section: Physiological Levels Of H 2 S Exert Neuroprotective Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen sulfide, or molecules with similar capabilities, provides a possible therapeutic approach to treating individuals with life-threatening events that compromise oxygen delivery to vital organs (Aslami et al, 2010;Szabo, 2007;Wagner et al, 2009). Like many new ideas that address biologically and medically complex problems, the ability to use basic sciences from model systems to identify treatments and therapeutics for the benefit of human health related issues is going to be costly, perhaps controversial and quite complex at the biological level (Olson, 2011). However, given the profound effect oxygen deprivation, including anoxia, has on living systems it is of great interest to continue the onward march toward understanding the molecular nature of anoxia tolerance in biological systems.…”
Section: Conclusion -Suspended Animation and Human Health Related Ismentioning
confidence: 99%